The Emergence of Autoclitic Frames in Atypically and Typically Developing Children as a Function of Multiple Exemplar Instruction - Luke, Nicole (The Society for the Experimental Analysis of Behavior, Inc, 2011)
In two experiments, we tested the effect of multiple exemplar instruction (MEI) for training sets on the emergence of autoclitic frames for spatial relations for novel tacts and mands. In Experiment 1, we used a replicated pre- and post-intervention probe design with four students with significant learning disabilities to test for acquisition of four autoclitic frames with novel tacts and mands before and after MEI. The untaught topographies emerged for all participants. In Experiment 2, we used a multiple probe design to test the effects of the MEI procedures on the same responses in four typically developing, bilingual students. The novel usage emerged for all participants. In the latter experiment, the children demonstrated untaught usage of mand or tact frames regardless of whether they were taught to respond in either listener or speaker functions alone or across listener and speaker functions. The findings are discussed in terms of the role of MEI in the formation of abstractions.